2008
DOI: 10.1007/s00109-008-0368-5
|View full text |Cite
|
Sign up to set email alerts
|

A central role for free heme in the pathogenesis of severe malaria: the missing link?

Abstract: Malaria, the disease caused by Plasmodium infection, is endemic to poverty in so-called underdeveloped countries. Plasmodium falciparum, the main infectious Plasmodium species in sub-Saharan countries, can trigger the development of severe malaria, including cerebral malaria, a neurological syndrome that claims the lives of more than one million children (<5 years old) per year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
212
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(233 citation statements)
references
References 97 publications
10
212
1
2
Order By: Relevance
“…The oxidative stress response orchestrated by the transcription factor, nuclear factor E2-related factor-2 (NRF2) 27,28 (Figure 2) can contribute critically to the establishment of disease tolerance to infection, as demonstrated for malaria 20,29 . Briefly, the blood stage of Plasmodium infection is associated with hemolysis and hence with generation of extracellular hemoglobin 20,21,29,30 . Upon oxidation, extracellular hemoglobin releases its prosthetic heme groups, which act as catalysts in the production of reactive oxygen species (ROS) and nitrogen species (RNS).…”
Section: Stress Responses In Tissue Damage Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…The oxidative stress response orchestrated by the transcription factor, nuclear factor E2-related factor-2 (NRF2) 27,28 (Figure 2) can contribute critically to the establishment of disease tolerance to infection, as demonstrated for malaria 20,29 . Briefly, the blood stage of Plasmodium infection is associated with hemolysis and hence with generation of extracellular hemoglobin 20,21,29,30 . Upon oxidation, extracellular hemoglobin releases its prosthetic heme groups, which act as catalysts in the production of reactive oxygen species (ROS) and nitrogen species (RNS).…”
Section: Stress Responses In Tissue Damage Controlmentioning
confidence: 99%
“…Upon oxidation, extracellular hemoglobin releases its prosthetic heme groups, which act as catalysts in the production of reactive oxygen species (ROS) and nitrogen species (RNS). This can lead to oxidative stress and cellular damage in host parenchyma tissues 12,13,16,31 , driving the pathogenesis of severe forms of malaria 30 .…”
Section: Stress Responses In Tissue Damage Controlmentioning
confidence: 99%
“…Cell-free hemoglobin released during the blood stage of Plasmodium infection promotes tissue oxidation and organ failure [101]. Animal models have shown that HO-1, encoded by the stress-inducible gene Hmox1, can protect the tissues from the heme toxic effect independently of pathogen load [102].…”
Section: Induction Of Antioxidant Mechanismsmentioning
confidence: 99%
“…Animal models have shown that HO-1, encoded by the stress-inducible gene Hmox1, can protect the tissues from the heme toxic effect independently of pathogen load [102]. Such a mechanism could explain the protection mediated by sickle cell anemia [101]. …”
mentioning
confidence: 99%
“…Evidence from previous studies have shown that haem, the substrate of HO‐1, is also its major inducer 15, 16, 17, 20, 33, and when cells are exposed to haem there is an increased expression of HO‐1 to catabolize haem and prevent its cytotoxicity 33. As patients with the HbAS genotype have higher levels of haem compared with HbAA genotype at convalescence, we investigated the possibility of a corresponding induction of HO‐1 in both genotypes.…”
Section: Discussionmentioning
confidence: 99%